Pengaruh Penggunaan Media Kartu Domat Pecahan Matematika Terhadap Hasil Belajar Kelas III - Qurota Ayun, Fitria; Rachmania, Desty Dwi (IJPSE Indonesian Journal of Primary Science Education, 2024)
In this study, there is a problem, namely students do not understand the meaning of teacher fractions using learning media that are not in accordance with mathematical fraction material and low student learning outcomes on mathematical fraction material. The purpose of this study was to determine the results before and after using domat card media and to determine the effect of using class III domat card media SD Negeri Pakel 1 Bareng Jombang. This study uses quantitative research with an experimental type which uses the help of SPSS software or (statiscal package for social scince) version 22. The results of this study can be concluded that there is the ability of SD Negeri Pakel 1 students totaling 21 students, namely being able to understand fractional material using domat card media. In this study took data with pre-test and post-test. Where with the average pree test score of 55.85, and the Post test score of 82.19. In this study, the influence of learning using Domat card media shows that there is a significant difference of 0.000 smaller than 0.5, so it can be stated that this research affects student learning outcomes in understanding fractional material using Domat card media.